Resting-state EEG gamma power and theta–gamma coupling enhancement following high-frequency left dorsolateral prefrontal rTMS in patients with depression. Issue 3 (March 2017) - Noda, Yoshihiro; Zomorrodi, Reza; Saeki, Takashi; Rajji, Tarek K.; Blumberger, Daniel M.; Daskalakis, Zafiris J.; Nakamura, Motoaki
Highlights: Resting-state EEG gamma power and theta–gamma coupling (TGC) were significantly increased following rTMS in depression. Increased gamma power at the left prefrontal area correlated with improvement of the HAM-D17 and BDI. Increased TGC at the left central area correlated with improvement in the number of errors on WCST. Abstract: Objective: We aimed to investigate neuromodulatory effects of high-frequency left dorsolateral prefrontal cortex repetitive transcranial magnetic stimulation (rTMS) on resting-state electroencephalography (EEG) and their clinical and cognitive correlates in patients with depression. Methods: Thirty-one patients diagnosed with depression included in the present study. Resting-state gamma power and theta–gamma coupling (TGC) were calculated before and after a course of rTMS. We explored the relationship among gamma power, TGC, and clinical/cognitive outcomes as measured with the Hamilton Rating Scale for Depression (HAM-D17 ), Beck Depression Inventory (BDI), and Wisconsin Card Sorting Test (WCST). Results: Following rTMS, depressed patients demonstrated significant increases of resting gamma power at the F3 and F4 electrode sites and resting TGC at the C3 and T3 electrode sites. Furthermore, the increased gamma power at the F3 electrode site was significantly correlated with improved score on the HAM-D17 and BDI, while the increased TGC at the C3 electrode site was significantly correlated with reduced number of errors on the WCST. Conclusion: Thus, resting-state gamma power and TGC may represent potential biomarkers of depression associated with therapeutic effects of rTMS. Significance: Resting-state EEG may provide potential biomarkers related to therapeutic effects of rTMS.